Stability-Indicating RP-HPLC Method for the Quantification of Paliperidone in Bulk and Solid Dosage Form to Establish Validation and Stability Indicating Parameters - Rudragangaiah, Sadashivaiah; Bhatta, Rohith Ganapathi; Kotappa, Satheesha Babu Birur (Indian Journal of Pharmaceutical Education and Research, 2019)
Objectives: In the present research work, stability indicating reverse phase high performance liquid chromatography method was developed and validated for the quantification of paliperidone in bulk and solid dosage form. Materials and Methods: The chromatographic separation of paliperidone was carried out using Phenomenex, Gemini NX, Octadecyl silane column (150x4.6 mm, 5 µm, particle size) with the mobile phase consisting of methanol: acetonitrile: 0.15% v/v triethylamine in water (pH 6) in the ratio of 50:20:30 v/v, flow rate was determined at 1 ml/min. UV detection wavelength was observed at 237 nm. Method validation and stress testing was carried out as per ICH guidelines Q2 (R1) and Q1A (R2) to demonstrate the suitability and specificity of the method. Results: The developed method had shorter retention time of 3.2 min. The RSD for system, method and intermediate precision in all instrumental condition was found to be less than 2% and the mean recovery was found to be 100.64%. Linearity range was obtained at concentration range of 7.5-150 µg/ml with a regression coefficient (R2) of 0.999. Detection and quantification limits for paliperidone were found to be 0.14 and 0.42 µg/ml, respectively. The developed method could separate the potential degradation products from the analyte peak. Conclusion: The results of validation were found to be satisfactory in all tested validation parameters suggested that the developed method is specific, precise, accurate and robust. Hence, this method would be applied for quantification of paliperidone in bulk and solid dosage form.
Keywords: Paliperidone; RP-HPLC; Stability of analytical solution; Validation; Stress; testing